Graphene Transfer: A Mechanism for Highly Efficient Electrochemical Bubbling Delamination of CVD‐Grown Graphene from Metal Substrates (Adv. Mater. Interfaces 8/2016). Issue 8 (April 2016) - Liu, Lihui; Liu, Xin; Zhan, Zhaoyao; Guo, Weiling; Xu, Chen; Deng, Jun; Chakarov, Dinko; Hyldgaard, Per; Schröder, Elsebeth; Yurgens, August; Sun, Jie
Abstract : The efficient/nondestructive electrochemical bubbling delamination method for graphene transfer can alleviate the cost and pollution problems during the traditional metal chemical etching process. In article number 1500492, Lihui Liu and co‐workers reveal the screening mechanism of the nonreactive ions in the electrolyte based on the capacitor circuit model. The graphene delamination time decreases 27 times by increasing the NaOH ratio in the electrolyte due to the enhanced screening effect.